PENGARUH MODAL PSIKOLOGIKAL TERHADAP KETERIKATAN MAHASISWA YANG DIMEDIASI OLEH PEMBERDAYAAN BELAJAR PADA MAHASISWA S1 FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS SYIAH KUALA - Vina Dhiean Agustina; Megawati Megawati (Departemen Manajemen, 2019)
This study aims to measure the effect of Psychological capital on student Engagement which is mediated by Learning Empowerment in S1Economics and Business undergraduate students at Syiah Kuala University. The sample used in this study was 240 undergraduate student in odd semester 2018/2019 with a total 240 respondents. Data collection equipment used in this study was a questionnaire. The sampling technique used was Proportionated Stratified Random Sampling. Hierarchical Linear Modelling (HLM) was used as a method of analysis to determine the effect of all the variables involved.Based on the result of the HLM analysis indicated that Psychological Capital positively influence students Engagement, Psychological Capital Positively influence Learning Empowerment, Learning Empowerment positively influence Students Engagement and Learning Empowerment mediate the relationship between Psychological Capital and Studens Engagement.